Tyrosine kinase participates in alpha 1A-adrenoceptor-mediated increase of intracellular calcium in human embryo kidney 293 cells. - Zhu Wei-zhong; Gao Ben-bo; Li He-wang; Zhang You-yi; Han Qi-de (Acta Pharmacologica Sinica, 2016)
AIM: To determine the role of protein-tyrosine kinase (PTK) in alpha 1A-adrenoceptor-mediated increase of [Ca2+]i (intracellular calcium) in human embryo kidney (HEK) 293 cells expressed alpha 1A-adrenoceptor. METHODS: Effects of two PTK inhibitors: genistein and tyrphostin, were investigated on the increase of [Ca2+]i by using Fura-2, The activity of PTK was measured and the accumulation of [3H] InsPs were observed. RESULTS: Norepinephrine stimulated a rapid increase in [Ca2+]i to (371 +/- 31) nmol.L-1 in HEK 293 cells. Norepinephrine-induced increase of [Ca2+]i was inhibited by the tyrosine kinase inhibitors quercetin and tyrphostin by 23.8% and 21.4%, respectively, but the accumulation of [3H]InsPs induced by norepinephrine was not. The activity of the plasma-associated tyrosine kinase was increased to (1.73 +/- 0.72)-fold over the control by norepinephrine 10 mumol.L-1. The norepinephrine-activated PTK was inhibited by calphostin C and depletion of intra- and extra-cellular Ca2+. CONCLUSION: The PTK participates in mobilization of Ca2+ mediated by alpha 1A-adrenoceptors in HEK 293 cell lines.